A case–control analysis of maternal diet and risk of neural tube defects in Bangladesh. Issue 14 (15th April 2019) - Obrycki, John F.; Lee, Jane J.; Kapur, Kush; Paul, Ligi; Hasan, Md Omar Sharif Ibne; Mia, Selim; Quamruzzaman, Quazi; Christiani, David C.; Mazumdar, Maitreyi
Abstract: Objectives: Mothers need a nutrient‐rich diet for healthy neural tube development. Neural tube defect risk can be reduced through fortifying grain products with folic acid and taking folic acid supplements. Fortification is not required in Bangladesh. Maternal supplement use rates are low, similar to other countries. This study evaluates maternal dietary intake during pregnancy to identify possible interventions. Methods: A food frequency questionnaire (FFQ) assessed maternal diet. The primary aim compared dietary intake (calories, fat, carbohydrate, protein, fiber, vitamins, and minerals) between mothers of infants with myelomeningocele (cases) and mothers of controls. Secondary aims included (i) comparing foods consumed and (ii) evaluating if rice intake correlated with arsenic exposure. Paired t ‐tests, Wilcoxon signed rank tests, McNemar's chi‐squared test, and linear regression were used. Results: This study included 110 matched mother–infant pairs (55 cases/55 controls). Mothers of cases and mothers of controls had similar caloric intake [median 2406 kcal/day vs. 2196 kcal/day ( p  = 0.071)]. Mothers in both groups consumed less than half the daily recommended 600 μg of folate. Diets were potentially deficient in vitamins A, D, E, potassium, sodium, and iron. Steamed rice was the primary food consumed for both groups, and this rice intake was not associated with toenail arsenic. Conclusions: Dietary interventions should increase folate, vitamins A, D, E, potassium, sodium, and iron intake in Bangladeshi mothers. Folic acid fortification of grain products maybe the only viable strategy to achieve adequate folate intake for mothers. Given the central role of rice to the Bangladeshi diet, fortifying rice may be a viable option.